Wee1 Inhibitor AZD1775 Effectively Inhibits the Malignant Phenotypes of Esophageal Squamous Cell Carcinoma In Vitro and In Vivo - Bi, Shuning; Wei, Qiuren; Zhao, Zhijun; Chen, Liang; Wang, Chaojie; Xie, Songqiang (Frontiers in Pharmacology, 2019)
Esophageal squamous cell carcinoma (ESCC) is a common malignant diagnosed cancer with increasing incidence rate and few treatment options. As a specific small-molecule inhibitor of the Wee1 tyrosine kinase, AZD1775 has been previously showed potent antitumor effect on multiple types of cancer in various preclinical studies and clinical trials. However, the expression of Wee1 and the role of AZD1775 in ESCC remain unclear. In the present study, we found that the expression of Wee1 was much higher in ESCC cell lines and clinical samples than that of the corresponding controls. In addition, we demonstrated that AZD1775 exhibited strong inhibitory effect against Wee1 kinase in both tested ESCC cells at nanomolar concentrations. Moreover, AZD1775 effectively suppressed ESCC cell growth, and triggered apoptosis via the mitochondrial-dependent signaling pathway. AZD1775 also diminished cell migration and invasion, as well as the expression of MMP-2 and MMP-9. Interestingly, knockdown of Wee1 displayed a similar inhibitory effect of AZD1775 on ESCC cells. In addition, there was a synergism between AZD1775 and 5-fluorouracil or cisplatin in inducing cell death. More importantly, the in vivo experiments also demonstrated that AZD1775 potently inhibited ESCC cell growth and metastasis. In summary, our data suggest that the Wee1 inhibitor AZD1775 may be a potential therapeutic agent and warrants a clinical trial for patients with ESCC, even those with metastasis.